An ordered copper nanowell-array film with near-perfect broadband absorption from ultraviolet to near-infrared light. (29th October 2020) - Shen, Juan; Ren, Yong; Zhu, Xinxin; Mao, Min; Zhou, Quan; Zhou, Rui; Dai, Bo; Li, Xinxi
Abstract: A copper film with the well arrays structure is prepared by magnetron sputtering in an anodic aluminum oxide (AAO) template. The ultraviolet–visible absorption spectra indicate that the light absorbance of the film is as high as 99.6% in the wavelength range of 200–2500 nm. The copper nanowell-array film exhibits a strong absorptance at the spectral range of 200–2500 nm owing to light trapped in the nanowell-array structures, the interband transition of copper, and the surface plasmon resonances of copper nanowell-arrays. This near-perfect broadband light absorption from UV–vis–NIR might improve greatly the utilization of light.